COVID-19 Impact on the National Tuberculosis Elimination Program Guidelines and Its Relevance to the Indian Population - Sriram Krishnamoorthy; Kalpana Ramachandran (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
The COVID-19 pandemic caused a severe dent in the decades of progress achieved in tuberculosis control and elimination measures, indicating that these measures need to be more structured and resilient. This manuscript focuses on the impact of the COVID-19 pandemic on TB control and also on the measures taken by the Government of India in effectively combating this syndemic. The main objective is to emphasise the impact of the COVID-19 pandemic on TB control and also to highlight the various innovative initiatives taken by the Government of India to keep the spread of tuberculosis under check. The positive trends in tuberculosis elimination strategies observed till 2019 showed a dramatic reversal after the onset of the COVID-19 pandemic. Biological interactions between tuberculosis and COVID-19 agents, lung parenchymal damage occurring in both diseases, multiple lockdowns, the reduced workforce at tuberculosis notification centres, and reallocation of funds to control the new-onset pandemic were some of the reasons for the decline in overall notifications across the globe. The National Tuberculosis Elimination Programme initiated a holistic approach to eliminate TB from South Asia by 2030. Innovative strategies like digitalisation of service delivery systems, telemedicine consultations, and a four-tier hierarchy system resulted in a rise in the number of tuberculosis notifications. Making this campaign a public movement, creating Public Support Groups and propagating an online Nikshay portal for tuberculous notification greatly facilitated efforts to create a tuberculosis-free world. Despite the COVID-19 pandemic causing a temporary slowdown, digitalisation processes and various innovative strategies have kept disease elimination hopes still alive. The government alone may not be able to accomplish this goal. By increasing the Government’s responsibility and accountability, facilitating an effective coalition with communities and civil societies, protecting human rights, promoting ethics in treatment, enhancing the equity of distribution of effective treatment across the community, and calling for global collaboration in setting up strategic goals/targets at the national level, the world could be TB-free by 2035. Combined efforts and collective responsibility from the public, medical, and para-medical support staff are imperative in making this dream of a tuberculosis-free society, soon a reality.